Numerical investigation of Reynolds number effects on vortex-induced vibrations at low and moderate Re regimes - Gu, Jian; Fernandes, Antonio Carlos; Han, Xiangxi; Kuang, Xiaofeng; Chen, Wei (Ocean engineering, 2022)
Reynolds number effects on vortex-induced vibration are paid more and more attention, as the reliability and efficiency of risers, pipelines and cables becoming crucial to the performance of production system installed in deep water. Since its strong nonlinearities and correlations to multi-factors on both structure and fluid characteristics, Re effects are still far to be fully understood. In the present article, numerical studies are implemented on an elastically mounted circular cylinder at low and moderate Re regimes (Re = 100–1650, 1700–27000) respectively, under the circumstances of low mass-damping. Re effects are investigated extensively on the response amplitude, frequency, drag, lift coefficient and also vortex-shedding patterns. In overall, Re effects are found more prominent at the moderate Re than that at the low Re regime. Specifically, the significant response amplitudes are found more sensitive to the Re variation than the significant frequency and hydrodynamic coefficients at both Re regimes. The peak amplitude and synchronization region are revealed to increase with the increase of Re at the moderate regime. In addition, the effectiveness of α is further validated in characterizing the correlation between Re and U* among different oscillatory systems. •Re effects are comprehensively investigated on structural dynamics and vortex-shedding patterns.•The Re effects are found more prominent at the moderate Re regime than that at the low Re regime.•The response amplitude is found more sensitive to Re differences than the response frequency and hydrodynamic coefficients.•The parameter alpha is further validated able to coordinate the responses of different oscillatory systems.